New records of coral-associated crabs (Decapoda: Brachyura: Carpilioidea, Trapezoidea) from Easter Island - Boyko, Christopher B.; Mendoza, Jose C. E.; Castro, Peter (Zootaxa, 2017)
A review is made of those brachyurans that are symbiotic or otherwise associated with scleractinian corals on Easter Island, southeastern Pacific Ocean. A total of seven species is reported, including three species from two families not previously known from the island. Earlier records of Trapezia are analyzed and, although as many as six species have been previously reported, we conclude that only three species are known to occur on the island with certainty.